Illustrating BASIC, a simple programming language - Alcock, Donald, 1930- (Cambridge [Eng.] ; New York : Cambridge University Press, 1977)
Presents a popular computer language called BASIC and explains how to write simple programs in it.
Includes index.
Keywords: BASIC (Computer program language); BASIC (Computer program language); Programming languages (Computers)